Studies on Some Lanthanide(III) Complexes of 2-N-(m-Phenoxybenzylidine)furfurylamine - Kumar , ADESH; DAS, SHANU; DHAKAREY, RAJESH (Asian Journal of Chemistry, 2010)
Complexes of La(III), Pr(III), Nd(III), Sm(III) and Gd(III) with 2-N-(m-phenoxybenzylidine)furfurylamine have been synthesized and characterized by elemental analysis, magnetic susceptibility measurements, infrared, NMR and electronic spectral data. It is proposed that the ligand is bidentate ON donor in the complexes.